From the Archives of Levon Mkrtchyan: Naum Grebnev’s Letters to Levon Mkrtchyan - SAHAKYANC, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
Undertaking the translation and publication of Armenian medieval poetry, especially “Book of Lamentations” by Grigor Narekatsi had a special place within the scope of academician Levon Mkrtchyan’s activity. Since 1960-s Levon Mkrtchyan initiated the realization of a number of activities involving Naum Grebnev – a well-known expert in the art of translation. The published letters are evidence of the efforts owing to which the works of Armenian medieval poets, especially Kuchak, Narekatsi, were published in Russian and highly appreciated.
Keywords: Armenian poetry, translation, Kuchak, Narekatsi